Settlement delays in the money market - Leonardo Bartolini; Spence Hilton; James McAndrews (Federal Reserve Bank of New York, 2008)
We track 38,000 money market trades from execution to delivery and return to provide a first empirical analysis of settlement delays in financial markets. In line with predictions from recent models showing that financial claims are settled strategically, we document a tendency by lenders to delay delivery of loaned funds until the afternoon hours. We find that banks follow a simple strategy to manage the risk of account overdrafts - delaying the settlement of large payments relative to that of small payments. More sophisticated strategies, such as increasing settlement delays when own liquid balances are low and when dealing with small trading partners, play a marginal role. We also find evidence of strategic delay in the return of borrowed funds, although we can explain a smaller fraction of the dispersion in delays in the return than in the delivery leg of money market lending.
Keywords: G21; C78; L14; 330; Money market trading; settlement delay; gridlock equilibria; Geldmarkt; Refinanzierung; Anlageverhalten; Zahlungsverkehr; Spotmarkt; Theorie; USA